Modeling of Linguistic Reference Schemes - Halpin, Terry (IGI Global, 2015)
When using natural language, people typically refer to individual things by using proper names or definite descriptions. Data modeling languages differ considerably in their support for such linguistic reference schemes. Understanding these differences is important for modeling reference schemes within such languages and for transforming models from one language to another. This article provides a comparative review of reference scheme modeling within the Unified Modeling Language (version 2.5), the Barker dialect of Entity Relationship modeling, Object-Role Modeling (version 2), relational database modeling, and the Web Ontology Language (version 2.0). The author identifies which kinds of reference schemes can be captured within these languages as well as those reference schemes that cannot be. The author's analysis covers simple reference schemes, compound reference schemes, disjunctive reference and context-dependent reference schemes.